First Nations, Settler Parliaments, and the Question of Consultation: Reconciling Parliamentary Supremacy and Indigenous Peoples’ Right to Self-Determination - Hobbs, Harry (Osgoode Hall Law Journal, 2021)
First Nations peoples assert a right to a distinctive relationship with the state based on their pre-colonial status as self-governing sovereign communities. Ascertaining the scope of First Nations peoples’ collective right to self-determination is complex, but there is broad international agreement that it encompasses a right to be consulted on state action that will affect their interests, including in the law-making process. The problem is that the right to be consulted in the development of legislation appears to place a constraint on the power of the legislature to propose, debate, amend, and enact laws as they see fit. Does the right to consultation unduly or impermissibly fetter democratic government by imposing a procedural or substantive restriction on the introduction of proposed laws? Can this entitlement be reconciled with the constitutional value of parliamentary supremacy? In recent years, the highest courts in Australia, Canada, and Aotearoa New Zealand have explored these questions. This paper examines those decisions and considers their consequences for the appropriate constitutional relationship between First Nations Peoples and the State.